2021
DOI: 10.3390/microorganisms9051030
|View full text |Cite
|
Sign up to set email alerts
|

Oral Microbiota of Children Is Conserved across Han, Tibetan and Hui Groups and Is Correlated with Diet and Gut Microbiota

Abstract: The oral microbiota can be affected by several factors; however, little is known about the relationship between diet, ethnicity and commensal oral microbiota among school children living in close geographic proximity. In addition, the relationship between the oral and gut microbiota remains unclear. We collected saliva from 60 school children from the Tibetan, Han and Hui ethnicities for a 16S rRNA gene sequencing analysis and comparison with previously collected fecal samples. The study revealed that Bacteroi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 66 publications
1
13
0
Order By: Relevance
“…Many host characteristics can impact upon the composition of the salivary microorganisms, including age 16 , diet 17,18 , ethnicity 19 , gender 20 , smoking 21 , alcohol use 22 , circadian rhythm 23 , body mass index 24 and the type of stimulation 25 . Some studies have correlated the diverse microbiome with the distinct sensory responses between consumer groups 26,27 .…”
Section: Introductionmentioning
confidence: 99%
“…Many host characteristics can impact upon the composition of the salivary microorganisms, including age 16 , diet 17,18 , ethnicity 19 , gender 20 , smoking 21 , alcohol use 22 , circadian rhythm 23 , body mass index 24 and the type of stimulation 25 . Some studies have correlated the diverse microbiome with the distinct sensory responses between consumer groups 26,27 .…”
Section: Introductionmentioning
confidence: 99%
“…However, it is worth noting that the relationship between the oral and gut microbiota is not consistent among different species. For example, the oral microbiota is associated with the gut microbiota in human children ( Liu et al, 2021 ), but much less so in the great tit Parus major ( Kropáčková et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…More studies on the gut bacteria of Tibetans, Mongolians, Hui, and Zhuang were indicated by the study material, with publications on the Tibetans’ gut microorganisms appearing the most frequently. Some research focused on the variations in the prevalence of the same disease among various ethnic groups, which are brought on by various gut bacteria among ethnic minorities ( Liao et al., 2018 ; Li et al., 2021 ; Liu et al., 2021a ). Other research have demonstrated a strong correlation between Tibetans’ gut bacteria and the high prevalence of endemic diseases in ethnic minority locations, such as coronary heart disease ( Ma et al., 2021 ).…”
Section: The State Of Gut Microbiota Research In China’s Ethnic Minor...mentioning
confidence: 99%
“…Other research have demonstrated a strong correlation between Tibetans’ gut bacteria and the high prevalence of endemic diseases in ethnic minority locations, such as coronary heart disease ( Ma et al., 2021 ). Numerous research on the gut microbiota of ethnic minorities also take into account geography and way of life in addition to ethnicity ( Liu et al., 2021b ).…”
Section: The State Of Gut Microbiota Research In China’s Ethnic Minor...mentioning
confidence: 99%